Cytoarchitecture, intersubject variability, and 3D mapping of four new areas of the human anterior prefrontal cortex - Bruno, Ariane; Bludau, Sebastian; Mohlberg, Hartmut; Amunts, Katrin (Frontiers in Neuroanatomy, 2022)
The dorsolateral prefrontal cortex (DLPFC) plays a key role in cognitive control and executive functions, including working memory, attention, value encoding, decision making, monitoring, and controlling behavioral strategies. However, the relationships between this variety of functions and the underlying cortical areas, which specifically contribute to these functions, are not yet well-understood. Existing microstructural maps differ in the number, localization, and extent of areas of the DLPFC. Moreover, there is a considerable intersubject variability both in the sulcal pattern and in the microstructure of this region, which impedes comparison with functional neuroimaging studies. The aim of this study was to provide microstructural, cytoarchitectonic maps of the human anterior DLPFC in 3D space. Therefore, we analyzed 10 human post-mortem brains and mapped their borders using a well-established approach based on statistical image analysis. Four new areas (i.e., SFS1, SFS2, MFG1, and MFG2) were identified in serial, cell-body stained brain sections that occupy the anterior superior frontal sulcus and middle frontal gyrus, i.e., a region corresponding to parts of Brodmann areas 9 and 46. Differences between areas in cytoarchitecture were captured using gray level index profiles, reflecting changes in the volume fraction of cell bodies from the surface of the brain to the cortex-white matter border. A hierarchical cluster analysis of these profiles indicated that areas of the anterior DLPFC displayed higher cytoarchitectonic similarity between each other than to areas of the neighboring frontal pole (areas Fp1 and Fp2), Broca's region (areas 44 and 45) of the ventral prefrontal cortex, and posterior DLPFC areas (8d1, 8d2, 8v1, and 8v2). Area-specific, cytoarchitectonic differences were found between the brains of males and females. The individual areas were 3D-reconstructed, and probability maps were created in the MNI Colin27 and ICBM152casym reference spaces to take the variability of areas in stereotaxic space into account. The new maps contribute to Julich-Brain and are publicly available as a resource for studying neuroimaging data, helping to clarify the functional and organizational principles of the human prefrontal cortex.